Effect of herbicides on the growth of beneficial microorganisms in rhizospheric soil - Vera, José; Sarango, Yessenia; Villamar, Mónica; Ortiz, Jhonny; Sevilla-Carrasco, Jaime; Duarte, Josue; Lucas, Leonel (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
This research seeks to understand the impact of herbicides on beneficial soil microorganisms, essential for agricultural health, and contribute to more sustainable management practices. The study aimed to evaluate the effect of herbicides commonly used in conventional agriculture, such as glyphosate, paraquat, and MCPA, on the growth of beneficial soil microorganisms. The microorganisms were isolated from the rhizosphere soil of a CCN-51 cacao crop from a production farm in Ecuador, and identified through morphological characterization and molecular analysis. The detected beneficial microorganisms were seeded in culture media with field-used doses of the different herbicides mentioned above, and mycelial growth in fungi (Trichoderma asperellum) and colony extension in bacteria (Bacillus subtilis and Pseudomonas fluorescens) were evaluated. The results showed that the herbicides had a significant inhibitory effect on the growth of these beneficial microorganisms. In the case of T. asperellum, paraquat and MCPA showed greater mycelial inhibition compared to glyphosate. Furthermore, all three herbicides significantly reduced the growth of B. subtilis and P. fluorescens, in contrast to the control groups, which maintained constant growth. These findings suggest that the herbicides studied may have a negative impact on the growth dynamics of beneficial microorganisms, which could affect the balance of the agricultural ecosystem. These results highlight the importance of considering the potential effects of herbicides on the soil microbiota in the management of sustainable agricultural systems.